2022
DOI: 10.1186/s12884-022-04899-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes of dual trigger with combination GnRH agonist and hCG versus trigger with hCG alone in women undergoing IVF/ICSI cycles: a retrospective cohort study with propensity score matching

Abstract: Background Despite a large number of studies on the selection of trigger drugs, it remains unclear whether the dual trigger with human chorionic gonadotropin (hCG) and gonadotropin-releasing hormone (GnRH) agonist, compared to the trigger with hCG alone, can improve the reproductive outcome of patients undergoing assisted reproductive technology. Therefore, this study aimed to compare the laboratory and clinical outcomes of dual trigger versus single trigger. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although the dual trigger protocol was superior in terms of increasing the total number of oocytes retrieved and the number of oocytes inseminated compared to the hCG protocol, the results of the present study showed that regarding to the number of follicles, the number of MII oocytes recovered, number of fertilized oocytes and number of IVM, both protocols were equivalent. Similar results were also found by other authors ( Ding et al ., 2017 ; Eser et al , 2018 ; Ben-Haroush et al , 2020 ; Oliveira et al ., 2021 ; Shapiro et al ., 2021 ; Dong et al ., 2022 ; Zhou et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dual trigger protocol was superior in terms of increasing the total number of oocytes retrieved and the number of oocytes inseminated compared to the hCG protocol, the results of the present study showed that regarding to the number of follicles, the number of MII oocytes recovered, number of fertilized oocytes and number of IVM, both protocols were equivalent. Similar results were also found by other authors ( Ding et al ., 2017 ; Eser et al , 2018 ; Ben-Haroush et al , 2020 ; Oliveira et al ., 2021 ; Shapiro et al ., 2021 ; Dong et al ., 2022 ; Zhou et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed the similarity between both protocols for triggering final oocyte maturation. Dong et al . (2022 ) investigated retrospectively whether a dual trigger for final oocyte maturation with a combination of a single dose of GnRH agonist and a standard dose of hCG could improve the reproductive outcomes compared with conventional hCG trigger alone.…”
Section: Discussionmentioning
confidence: 99%
“…Normal fertilization was confirmed when the presence of two pronuclei and the extrusion of the second polar body were observed 16–18 h after IVF/ICSI ( 9 , 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…Normal fertilization was confirmed when the presence of two pronuclei (2PN) and the extrusion of the second polar body(2PB) were observed 16–18 h after IVF/ICSI ( 14 , 15 ). Cleavage embryos were classified as high-quality embryos (grade I and II embryos) if they had seven to nine cells on day 3 and as same-sized blastomeres if with less than 20% blastomeric fragments.…”
Section: Methodsmentioning
confidence: 99%